Monitoring of equatorial plasma bubbles using aeronautical navigation system: a feasibility study - Keisuke Hosokawa; Susumu Saito; Hiroyuki Nakata; Chien-Hung Lin; Jia-Ting Lin; Pornchai Supnithi; Ichiro Tomizawa; Jun Sakai; Toru Takahashi; Takuya Tsugawa; Michi Nishioka; Mamoru Ishii (Earth, Planets and Space, 2023)
Abstract It has long been known that field-aligned irregularities within equatorial plasma bubbles (EPBs) can cause long-range propagation of radio waves in the VHF frequencies such as those used for TV broadcasting through the so-called forward scattering process. However, no attempt has been made to use such anomalous propagations of VHF radio waves for wide-area monitoring of EPBs. In this study, we investigated the feasibility of monitoring of EPBs using VHF radio waves used for aeronautical navigation systems such as VHF Omnidirectional radio Range (VOR). There are 370 VOR stations in the Eastern and Southeastern Asian region that can be potentially used as Tx stations for the observations of anomalous propagation. We have examined the forward scattering conditions of VHF waves using the magnetic field model and confirmed that it is possible to observe the EPB-related anomalous propagation if we set up Rx stations in Okinawa (Japan), Taiwan, and Thailand. During test observations conducted in Okinawa since 2021, no signal has been received that was clearly caused by anomalous propagation due to EPBs. This is simply because EPBs have not developed to high latitudes during the observation period due to the low solar activity. In March 2023, however, possible indications of EPB-related scattering were detected in Okinawa which implies the feasibility of observing EPBs with the current observation system. We plan to conduct pilot observations in Taiwan and Thailand in future to further evaluate the feasibility of this monitoring technique. Graphical Abstract